Physiotherapy Management of Frozen Shoulder Dextra E.C Dextra Shoulder Osteoarthritis Case - Widyaningrum, Ni Luh Gadung; Naufal, Adnan Faris; Efendi, Elif Nur (Universitas Muhammadiyah Surakarta, 2023)
Frozen Shoulder (FS) is a common shoulder disorder characterized by a gradual increase in pain that is direct and limited. Movement of the glenohumeral joint ranges of motion. The pathophysiology of frozen shoulder is relatively clear as a pathological process. The study used a case report study conducted at the Praktik Mandiri Fisioterapi Magetan. The cause of Frozen Shoulder is still unknown, but there are other factors that trigger the occurrence of frozen shoulder including postoperative fractures resulting in limited movement of the shoulder, certain diseases, injuries to surrounding muscles. Physiotherapy plays a role in optimizing children's active movements using interventions in the form of infrared modalities, myofacial release, scapular mobilization, approximation, GTO release, contract relax stretching, and ice packs. After being treated for 3 times T1-T3 there was an increase and change in muscle strength by measuring muscle strength by MMT, pain by NRS, LGS by goniometer, and functional ability by SPADI Index.